Inventaris Serangga Hama Pada Tanaman Hortikultura di Sumatera Barat - Kurniati, Rahmi; Novriyanti, Ernie (Experiment: Journal of Science Education, 2025)
Insect pests that attack horticultural agriculture in West Sumatra have resulted in reduced yields.  Accurate and detailed identification and inventory of pest species will facilitate appropriate control measures.This study aims to inventory the types of insect pests on horticultural crops in four areas of horticultural centers in West Sumatra.This study used a survey method to collect data through observations made randomly on several types of plants including cabbage, shallots, guava, eggplant and corn.Instruments used include 70% alcohol, label paper, tweezers, collection bottles and a mobile camera for documentation.From the results of the study, it is known that several types of insect pests in horticultural crops in several plantations in West Sumatra include cotton bollworm (Helicoverpa armigera),armyworm (Spodoptera litura), earthworm (Agrotis sp. ), mealybug (Paracoccus marginatus), fruit fly (Bactrocera dorsalis), Melamphaus rubrocinctus, ladybird (Epilachna sp.), leafhopper (Empoasca sp. ), whitefly (Bemisia tabaci), koksi beetle (Coccinella septempunctata), brown planthopper (Nilaparvata lugens), leaf beetle (Chaetocnema basalis) and turtle beetle (Aspidimorpha miliaris).The identification of pests on horticultural crops in West Sumatra shows variations in the types of pests that attack plants in each location. Pest control strategies need to be adapted to the type of plant and local environmental conditions.